EVALUATION OF EFFICACY OF BUSERELIN-DEPO IN PATIENTS WITH LOCALLY ADVANCED AND METHASTATIC PROSTATE CANCER - S. V. MISHUGIN (Медицинский совет, 2017)
Our surveillance was performed for 358 patients with locally advanced and disseminated prostate gland cancer who were treated by analogues of LHRH. Patients in group 1 (n = 222) received treatment with a LHRH analogue, and patients in group 2 (n = 136) received treatment with 75 mg Buserelin-depo 3. Experience has shown that the use of the Buserelin-Depot drug results in a regression of the average PSA value: Up to 36.05 ng/ml in 2 months, up to 12.35 ng/ml - in four months, up to 3.3 ng/ml - in six months. The drug ensures a steady decrease in the level of testosterone in the blood serum to the castration level already in a month after the start of treatment, a decrease in prostate gland volume (from 57.3 to 40.45 cc 3 by month 6 of treatment (-29.4%)). A number of patients have experienced a decrease in the need for analgesics and thus an increase in the activity status. The obtained data are comparable to those in the group of patients receiving other analogues of LHRH.